2015
DOI: 10.1038/srep12728
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a DYRK1A Inhibitor that Induces Degradation of the Target Kinase using Co-chaperone CDC37 fused with Luciferase nanoKAZ

Abstract: The protein kinase family includes attractive targets for drug development. Methods for screening of kinase inhibitors remain largely limited to in vitro catalytic assays. It has been shown that ATP-competitive inhibitors antagonize interaction between the target kinase and kinase-specific co-chaperone CDC37 in living cells. Here we show a cell-based method to screen kinase inhibitors using fusion protein of CDC37 with a mutated catalytic 19-kDa component of Oplophorus luciferase, nanoKAZ (CDC37-nanoKAZ). A du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 39 publications
2
45
0
Order By: Relevance
“…Our recent study indicated that mutations affecting autophosphorylation strengthen the interaction between DYRK1A and the kinase-specific co-chaperone CDC37 (ref. 36 ). CDC37 assists in the folding of target kinases in cooperation with HSP90 (refs 37 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent study indicated that mutations affecting autophosphorylation strengthen the interaction between DYRK1A and the kinase-specific co-chaperone CDC37 (ref. 36 ). CDC37 assists in the folding of target kinases in cooperation with HSP90 (refs 37 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether the mutation of Ser97 affects the thermodynamic stability of DYRK1A, we examined the interaction between the S97A mutant and CDC37 fused with luciferase nanoKAZ, as described in our recent study 36 , with some modifications (see the Methods for details). The S97A, Y321F, Y319F/Y321F and K188R mutations significantly strengthened the interaction of DYRK1A with CDC37-nanoKAZ ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, CDC37 fused to luciferase can be used as a thermodynamic sensor for kinase structures 11, 15 . Here we show that the pathogenic DYRK1B variants interact more strongly with CDC37 than wild DYRK1B.…”
Section: Discussionmentioning
confidence: 99%
“…In our past efforts with chemical library screening, we have developed anti‐viral compounds targeting hepatitis B virus (HBV), human herpesviruses, human immunodeficiency virus‐1 (HIV‐1), and dengue virus . In this study, we applied our screening system for HCV in combination with Rep‐Feo reporter replicon system, and identified retinoid derivative Tp80 as a potent inhibitor of HCV replication.…”
Section: Discussionmentioning
confidence: 99%
“…RT‐PCR was performed, as described previously . Briefly, total RNA was extracted from 1.0 × 10 5 of cells with Sepasol RNA‐I (Nacalai Tesque) and treated with RQ DNase I (Promega, Fitchburg, WI).…”
Section: Methodsmentioning
confidence: 99%